Simulated nitrogen deposition affects wood decomposition by cord-forming fungi. - Bebber, D; Watkinson, S; Boddy, L; Darrah, P (2011)
Anthropogenic nitrogen (N) deposition affects many natural processes, including forest litter decomposition. Saprotrophic fungi are the only organisms capable of completely decomposing lignocellulosic (woody) litter in temperate ecosystems, and therefore the responses of fungi to N deposition are critical in understanding the effects of global change on the forest carbon cycle. Plant litter decomposition under elevated N has been intensively studied, with varying results. The complexity of forest floor biota and variability in litter quality have obscured N-elevation effects on decomposers. Field experiments often utilize standardized substrates and N-levels, but few studies have controlled the decay organisms. Decomposition of beech (Fagus sylvatica) blocks inoculated with two cord-forming basidiomycete fungi, Hypholoma fasciculare and Phanerochaete velutina, was compared experimentally under realistic levels of simulated N deposition at Wytham Wood, Oxfordshire, UK. Mass loss was greater with P. velutina than with H. fasciculare, and with N treatment than in the control. Decomposition was accompanied by growth of the fungal mycelium and increasing N concentration in the remaining wood. We attribute the N effect on wood decay to the response of cord-forming wood decay fungi to N availability. Previous studies demonstrated the capacity of these fungi to scavenge and import N to decaying wood via a translocating network of mycelium. This study shows that small increases in N availability can increase wood decomposition by these organisms. Dead wood is an important carbon store and habitat. The responses of wood decomposers to anthropogenic N deposition should be considered in models of forest carbon dynamics.